Pengukuran Kinerja pada UD. Tahu Dua Saudara di Lapang dengan Menggunakan Model Balanced Scorecard - Fera Miranda,; Mhd. Rahmat Hidayat, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Dua Saudara is a small tofu processing business located on Jl. Letnan Mubin, Gampong Lapang, Johan Pahlawan District, West Aceh Regency, and has been operating since 2019. This business produces tofu made from local soybeans, characterized by its preservative-free and firm texture. The production process uses a combination of grinding machines and manual labor, involving seven employees. Despite having superior product characteristics and fairly stable market demand, the company still faces a number of challenges, such as fluctuations in soybean prices as the main raw material and the processing of odorous production waste, requiring special attention to maintain business sustainability and the comfort of the surrounding environment. In facing these various dynamics, a performance measurement tool is needed that emphasizes not only financial aspects, but also non-financial aspects to support the development of long-term business strategies. The Balanced Scorecard (BSC) is a performance measurement framework that assesses an organization from four perspectives: financial perspective, customer perspective, internal business process perspective, and growth and learning perspective. Through the implementation of the Balanced Scorecard, UD. Dua Saudara can identify the company's strengths and weaknesses, formulate a structured strategic direction, improve product quality, strengthen relationships with consumers, and enhance the capabilities of human resources within the company. This study aims to analyze the implementation of the Balanced Scorecard at UD. Dua Saudara as an approach to improving performance and developing business strategies.Using direct observation data, interviews, and documentation, the analysis shows that implementing the Balanced Scorecard has the potential to help companies maintain product quality excellence, manage production costs amid rising soybean prices, and improve internal process efficiency and employee skills. Thus, the Balanced Scorecard is a relevant and strategic tool for implementing in the management of small-scale tofu businesses such as UD. Dua Saudara in order to achieve better business sustainability.